Disturbance observer-based sliding mode control for multi-agent systems with mismatched uncertainties. Issue 5 (19th September 2018) - Wang, Qing; Sun, Changyin; Chai, Xiaofeng; Yu, Yao
Abstract : Purpose: This paper aims to develop sliding mode control (SMC) methods for second-order multi-agent systems (MAS) in the presence of mismatched uncertainties. Design/methodology/approach: Based on the disturbance observer (DOB), discontinuous and continuous sliding mode protocols are designed to achieve finite-time consensus in spite of the disturbances. Findings: Compared with integral SMC, numerical simulation results show that the proposed control methods exhibit better performance with respect to reduction of chattering. Originality/value: The main contributions are the following: MAS described with mismatched uncertainties are considered; both discontinuous and continuous sliding mode controllers are considered; with the proposed sliding mode controller, the desired sliding surface can be reached in finite time and the DOB is introduced in the controller to alleviate the chattering phenomenon.